Education for Sustainable Development in Foreign Language Learning: Content-Based Instruction in College-Level Curricula - de la Fuente, María J. (Routledge Research in Language Education, 2021)
This unique volume utilizes the UNESCO Education for Sustainable Development (ESD) framework to illustrate successful integration of sustainability education in post-secondary foreign language (FL) learning. Showcasing a variety of approaches to using content-based instruction (CBI) in college-level courses, this text valuably demonstrates how topics relating to environmental, social, and cultural dimensions of sustainability can be integrated in FL curricula. Chapters draw on case studies from colleges throughout the US and consider theoretical and practical concerns relating to models of sustainability-based teaching and learning. Chapters present examples of project-, problem-, and task-based approaches, as well as field work, debate, and reflective pedagogies to enhance students’ awareness and engagement with sustainable development issues as they acquire a foreign language. Insights and recommendations apply across languages and highlight the potential contribution of FL learning to promote sustainability literacy amongst learners. This text will benefit researchers, academics, and educators in higher education with an interest in Modern Foreign Languages, sustainability education, training, and leadership more broadly.